Soroepidemiologia da linfadenite caseosa em rebanhos de caprinos na zona rural de Mossoró-RN - Maia Neto, Antonio Alves (Universidade Federal Rural do Semi-Árido, 2020)
Caseous Lymphadenitis (CL) is an infectious disease that affects mainly small ruminants and is caused by the bacterium Corynebacterium pseudotuberculosis. The main focus of this study was to determine the seroprevalence of caseous lymphadenitis in the rural area in the city of Mossoró, RN and to evaluate the associated risk factors. Blood samples were collected from 385 goats in 13 farms around the rural area of Mossoró-RN. During the visits to the properties, a questionnaire related to the health sanitary system of the way that the animals were handled was applied and blood was collected through the venipuncture of the jugular, after previous cleanup in the region with cotton soaked in 70% alcohol and, in sterile tubes without anticoagulant. The serum was obtained by centrifugation for 10 minutes at 3000 rpm and the indirect ELISA test used the supernatant of the cp1002 strain of C. pseudotuberculosis and during the visit the questionnaire related to the hygiene sanitary system that the animals went through was carried out. Of the 385 goats’ sera tested, 90 samples (23.4%) showed positive results and 295 samples (76.6%) showed negative results and only 6 animals had clinical symptoms for LC. Of the 90 positive samples, 16 (17.6%) were male and 74 (25.2%) were female. Among the 295 (76.6%) negative samples, 75 (82.4%) were male and 220 (74.8%) were female and 6 animals presented clinical symptoms for CL. Out of the studied properties, 92.31% (12/13) were positive for Corynebacterium pseudotuberculosis, demonstrating the high dissemination of this agent in the city of Mossoró, RN. The age group between 3 and 6 years was the one with the highest seropositivity (60 animals), being 8 males and 52 females. The hygiene sanitary system performed on the animals on the properties was characterized by the absence of vaccination against CL and the isolation of the infected animals, and in 10 properties the abscesses were surgically removed, with the purulent material being disposed as follows: 7 bury, 2 burn and 1 dispose of in biological waste. Only 4 properties were performing quarantine to the newly acquired animals. It was concluded that the LC in goats in the city of Mossoró, RN is disseminated among the properties, with the majority of the animals were asymptomatic. In addition, most owners did not carry out proper animal hygiene sanitary system.
Keywords: Corynebacterium pseudotuberculosis; ELISA indireto; Epidemiologia; CIENCIAS AGRARIAS::MEDICINA VETERINARIA